Attributing Contemporary Leadership Models In Rasulullah (Peace Be Upon Him) - Zakaria bin Mat Zin; Faridah Hj. Hassan (Journal of Islamic Management Studies, 2018)
The purpose of this paper is to explore the contemporary leadership attributes of Rasulullah (pbuh). He has fulfilled perfectly the theories of transactional and transformational leadership. In fact, he took leadership to the next level when he was also seen as a spiritual leader which had never been showed in any world leaders neither before nor after his time. This paper also explains the foundation of akhlak or personality for every Muslim. Some principles were coined by some researches that were reviewed that simplified the understanding of the original principles from Quran and hadith/sunnah.